2014
DOI: 10.1890/es14-00356.1
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐sex‐biased tritrophic interactions on dioecious willow

Abstract: Abstract. Plant sex effects on herbivores are well studied, but little is known about these effects on predators and predator-herbivore dynamics. Here we take a holistic approach to study, simultaneously, plant sex effects on herbivore and predator preference and performance, as well as population densities and predation pressure in the field. For dioecious Salix cinerea (grey willow) we found that male plants represented higher host plant quality than females for an omnivorous predator (Anthocoris nemorum, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 37 publications
0
16
2
Order By: Relevance
“…Similarly, Boecklen et al (1990) found that male willows supported higher densities of five species of tenthredinid sawflies than do female willows. However, plant sex might also determine the structure of associated multitrophic communities (Petry et al 2013;Kabir et al 2014;Abdala-Roberts et al 2016). For example, Petry et al (2013) found higher predator to herbivore ratios on Valeriana edulis females relative to males.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Boecklen et al (1990) found that male willows supported higher densities of five species of tenthredinid sawflies than do female willows. However, plant sex might also determine the structure of associated multitrophic communities (Petry et al 2013;Kabir et al 2014;Abdala-Roberts et al 2016). For example, Petry et al (2013) found higher predator to herbivore ratios on Valeriana edulis females relative to males.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, it does so even though predation rates on female plants from the common flowerbug (Anthocoris nemorum L.), an anthocorid that is an omnivorous predator which feeds on P. vulgatissima eggs and Salix spp. nectar, are higher (Kabir et al, 2014). Such effects on insect preference and performance indicate that manipulating plant sex may be a powerful component of the IPM toolbox for Salix.…”
Section: Introductionmentioning
confidence: 99%
“…Plant sex is often an important trait structuring herbivory (Cornelissen and Stiling, 2005) in wild plants. Predation can also be affected by plant sex (Kabir et al, 2014;Mooney et al, 2012), and studies on its potential utility in IPM programs including dioecious crops are therefore merited. Previous studies have shown that wild male and female plants can differ with respect to both resistance and rewarding traits (Bañuelos et al, 2004;Boecklen et al, 1990;Bullock, 1984;Pollard and Briggs, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations